In vitro comparison of the cyclic fatigue resistance of HyFlex EDM, One G, and ProGlider nickel titanium glide path instruments in single and double curvature canals - Yılmaz, Koray (Restor Dent Endod, 2017)
OBJECTIVES: It was aimed to compare the cyclic fatigue resistances of ProGlider (PG), One G (OG), and HyFlex EDM (HEDM) nickel titanium glide path files in single- and double-curved artificial canals. MATERIALS AND METHODS: 40 PG (16/0.02), 40 OG (14/0.03), and 40 HEDM (10/0.05) single-file glide path files were used in the present study. Sixty files were subjected to cyclic fatigue test by using double-curved canals and 60 files by using single-curved canal (n = 20). The number of cycles to fracture (NCF) was calculated and the length of the fractured fragment (FL) was determined by a digital micro-caliper. Twelve pieces of fractured files were examined with scanning electron microscope to determine fracture types of the files (n = 2). The NCF and the FL data were analyzed using one-way analysis of variance and post hoc Tukey test using SPSS 21 software (p < 0.05). RESULTS: In all of the groups, NCF values were significantly lower in double-curved canals when compared to single-curved canals (p < 0.05). For both of single- and double-curved canals, NCF values of HEDM group in apical and coronal curvatures were found to be significantly higher than NCF values of PG and OG groups (p < 0.05). In both of single- and double-curved canals, NCF value of PG group was found significantly higher than OG group (p < 0.05). CONCLUSIONS: Within the limitations of this study, HEDM glide path files were found to have the highest cyclic fatigue resistance in both of single- and double-curved canals.